Estimates of parameters of random field regressions. I - Leonenko , N. N.; Le Fe Do, (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Asymptotic properties of the estimates of the modified method of least squares of regression parameters of random fields are investigated.